Soviet Contemporary Art : - From Thaw to Perestroika -. (Tokyo : Setagaya Art Museum, 1991)
Tselkov, Oleg ; Pyatnitsky, Vladimir ; Rabin, Oskar ; Yakoviev, Vladimir ; Veisberg, Vladimir ; Krasnopevtsev, Dmitri ; Nemukhin, Vladimir ; Rukhin, Ievgeni ; Plavinsky, Dmitri ; Kalinn, Yankilevsky, Vladimir ; Shteinberg, Eduard ; Roginsky, Mikhail ; Turetsky, Boris ; Chernishov, Michael ; Yulikov, Aleksandr ; Kabakov, Ilya ; etc
Soviet Contemporary Art - From Thaw to Perestroika - Setagaya Art Museum, Tokyo, 18 May - 23 June 1991
English-Japanese-Russian
kunstcatalogus
Keywords: RUSLAND